Assessing the Ecological Status of the Curug Tilu Leuwi Opat Waterfall Using Macroinvertebrates and Physicochemical Parameters - Hanif Syafrian Purnama; Tati Suryati Syamsudin; Dian Rosleine (Jurnal Biodjati, 2025)
Anthropogenic activities increasingly threaten freshwater availability. The Curug Tilu Leuwi Opat waterfall in the Cimahi River, an important water source for surrounding communities and a popular tourist site, requires an ecological assessment to support effective water management. This study aims to provide an initial overview of the ecological status of waters through an integrative approach that combines benthic macroinvertebrates and physicochemical parameters. Sampling was conducted in two waterfall streams, Kacapi and Aseupan, which are part of the Curug Tilu Leuwi Opat waterfall system. Physicochemical parameters measured included temperature, flow velocity, pH, dissolved oxygen, conductivity, and total dissolved solids. Benthic macroinvertebrates were collected using a Surber net and identified to the lowest feasible taxonomic level, typically morphospecies with some taxa at the family level, and subsequently analyzed using the Shannon–Wiener index, Simpson’s dominance, the Family Biotic Index (FBI), and Canonical Correspondence Analysis. Results indicated excellent water quality (FBI at Kacapi = 4.17; Aseupan = 4.24), driven by the presence of pollution-sensitive taxa from Leptophlebiidae, Tipulidae, and Perlidae, while the slightly higher FBI at Aseupan reflected several moderately tolerant families such as Physidae and Simuliidae. Benthic macroinvertebrate diversity was moderate with no dominant species, indicating stable community structure. Most measured parameters that met established standards met Class I criteria, while dissolved oxygen, conductivity, and flow velocity emerged as the dominant variables shaping community structure. Overall, the aquatic ecological status was excellent, highlighting the role of aquatic biodiversity as a scientific basis for sustainable environmental management